Red social facebook y su incidencia en el aculturalismo de los habitantes de la parroquia urbana Balzar de Vinces, cantón Vinces, provincia de los Ríos - Yépez Coronel, Jonathan Hamilton (2018)
The realization of this project seeks to generate a new alternative of information. Through observation, an attempt has been made to delimit the role of social networks and demonstrate how citizens, through their manifestations in networks, can also determine the issues to be addressed in the different media. In our analysis, we want to consider both the advantages of using social networks such as twitter or facebook when dealing with different current issues (immediacy, closeness, greater diffusion) and inconveniences (poor contrast of information, poor reliability of the source). All this is due to the fact that the internet has made access to information more and more simple but the network and especially social networks have managed to alter the traditional "Source - Journalist - Reader" scheme, provoking numerous information of bad quality and wrong. That is why we must define in this research whether we should consider social networks as a new type of information source or simply as a channel through which we can access the true source of information.